Classification of urban underlying surfaces in Beijing and its impact on summer high temperature and heat wave event - Zuofang Zheng; Guirong Xu; Nana Li; Hua Gao (Atmospheric Science Letters)
Abstract With analysis of local climate zone (LCZ) classification, approximately 52.0% of underlying surfaces in Beijing are covered by buildings with LCZ 5 (open midrise) accounting for the highest proportion, and LCZ D (low plants) is the most distributed among natural surface types. Compared to natural underlying surfaces, building underlying surfaces have higher values in the high temperature (HT) and heat wave (HW) days, HW intensity, and maximum HW duration. In recent decades, HT days on building underlying surfaces in Beijing start earlier and end later than those on natural underlying surfaces. Building underlying surfaces make greater contribution to urban heat island intensity of apparent temperature than to that of temperature, yet it is opposite for natural underlying surfaces.